External determinants of profitability of Jordanian Islamic and traditional banks - Tanash, Kholood Ahmed; Badarin, Abdalla Mohammad Al; Tanash, Hamza Ahmed (International Journal of Innovative Research and Scientific Studies, 2025)
This article aims to examine the external factors that impact the profitability of Jordanian Islamic and traditional banks. This paper was applied to all Jordanian banks: 3 Islamic banks and 12 traditional banks. The study was based on annual panel data for the years from 2011 to 2023. Data were collected from the annual reports of banks, reports of the Association of Banks in Jordan, and reports of the Central Bank of Jordan. The study used many determinants that affect profitability: ROA, Concentration Ratio (CR), Market Share (MR), gross domestic product (GDP), growth rate (GR), consumer price index (inflation) (CPI), and money supply (M2). The data were analyzed using a model of the effects of randomness. The paper found that Market Share (MR) and money supply (M2) have a positive impact on the profitability of Jordanian banks. It turned out that the Concentration Ratio (CR) and the consumer price index (CPI) have a negative impact on the profitability of Jordanian banks. It was also pointed out that gross domestic product (GDP) and growth rate (GR) have no impact on the profitability of Jordanian banks. The study recommends that Jordanian Islamic banks continuously monitor the development of their profits, as it affects their continuity and ability to compete. There is a need for Jordanian Islamic banks to explore new investment areas to exploit the volume of deposits available to them to increase profits.